A survey of modern algebra - Birkhoff, Garrett; Mac Lane, Saunders (New York : Macmillan; London : Collier-Macmillan, 1965)
In detail, Chapters 1-5 of the book center around the theory of linear and polynomial equations in commutative rings. Chapter 6 introduces non-commutative algebra through its simplest and most fundamental concept: that of a group. The group concept is applied systematically in Chapters 7 through 10, on vector spaces and matrices. Chapter 11 includes a completely revised introduction to Boolean algebra and lattice theory. Chapter 12 follows by a brief discussion of transfinite numbers. Finally, the last three chapters provide an introduction to general commutative algebra and arithmetic: ideals and quotient rings, extensions of fields, algebraic numbers and their factorization, and Galois theory.
Includes index.
Includes bibliographical references: p. 423-425.
ne 01/03/2018
Loans
Keywords: Algebra; Mathematics